Progress at the State Level Versus Recent Regress at the Federal Level: Changes in the Social Consequences of the U.S. War on Drugs. (June 2019) - Jensen, Eric L.; Mosher, Clayton; Gerber, Jurg; Angulski, Kate
Fifteen years ago, Jensen, Gerber, and Mosher drew attention to the societal costs of the U.S. war on drugs. They argued that while criminologists had focused on the impact of this war on the U.S. criminal justice system, other impacts had been under-researched. Whereas some research along these lines has been done that we review here briefly, some of the "objective" conditions of the war on drugs have changed in the intervening years. The primary aim of the current article is to update these conditions. In brief, we have witnessed progress at the U.S. state level in terms of adverse social consequences of the war on drugs, but a significant recent regress at the federal level. Among others, there are significant new restrictions to various federal programs, often disproportionately so for members of racial minorities.